PENGARUH MODEL STAD TERHADAP DAYA SERAP SISWA PADA PEMBELAJARAN ANSAMBEL PIANIKA KELAS VIII SMP - Atida, Icha Asih; Ismunandar, Ismunandar; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research aimed to determine the effect of cooperative learning model on STAD type on students’ absortion in learning pianika ensemble Grade VIII of SMPN 1 Ledo.This research was an experimental study using research design of one group pretest-posttes design. The independent variable in this research was the cooperative learning model of STAD type while the dependent variable was students’ absorption. The subjects of this research were students of Grade VIII A as many as 33 students. The data collection techniques used were interviews and tests. The data analysis techniques consisted of three stages. Those were the stage of data description, the stage of analysis requirement test and the stage of hypothesis test. The stage of data description included the distribution of students’ absorption data. The stage of analysis requirement test included normality test. While the stage of hypothesis testing used Paired T-test with a significance level of 5%. The calculation process used the computer of SPSS program version 17.0 for windows. The results showed that the application of the cooperative learning model of STAD type had a better performance towards increasing the students’ absorption in the learning of pianika ensembles in Grade VIII A of SMPN 1 Ledo.Keywords: model of STAD, absorption, pianic ansemble.